2016
DOI: 10.1007/s10661-016-5342-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes of soil carbon dioxide, methane, and nitrous oxide fluxes in relation to land use/cover management

Abstract: Conversions of land use/cover are associated with changes in soil properties and biogeochemical cycling, with implications for carbon (C), nitrogen (N), and trace gas fluxes. In an attempt to provide a comprehensive evaluation of the significance of different land uses (Alnus subcordata plantation, Taxodium distichum plantation, agriculture, and deforested areas) on soil features and on the dynamics of greenhouse gas (GHG) fluxes at local scale, this study was carried out in Mazandaran province, northern Iran.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In addition to climatic conditions, forest management practices/land use change could strongly influence soil‐atmosphere CO 2 exchange (Ju et al, ; Kooch et al, ; Wanyama et al, ). Our results revealed that soil CO 2 effluxes differed among the three forest types.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to climatic conditions, forest management practices/land use change could strongly influence soil‐atmosphere CO 2 exchange (Ju et al, ; Kooch et al, ; Wanyama et al, ). Our results revealed that soil CO 2 effluxes differed among the three forest types.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to climatic conditions, forest management practices/ land use change could strongly influence soil-atmosphere CO 2 exchange (Ju et al, 2016;Kooch et al, 2016;Wanyama et al, 2019).…”
Section: Effects Of Soil Properties and Microbial Communitymentioning
confidence: 99%
See 3 more Smart Citations